1994
DOI: 10.1002/anie.199423351
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the First Microporous Aluminum Phosphonate with Organic Groups Covalently Bonded to the Skeleton

Abstract: A hydrothermal procedure is used to prepare the molecular sieve Al2 (CH3PO3)3 (1). This compound has a new three‐dimensional framework, in which one six‐coordinate and two four‐coordinate Al centers are bound to the CH3PO3 units. The channel walls of the micropores of 1 are probably not lined with O atoms but with methyl groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
108
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(116 citation statements)
references
References 14 publications
6
108
0
2
Order By: Relevance
“…However, the first description of full three-dimensional inorganic framework containing organic groups was described by Maeda et al [76]. The authors described the direct hydrothermal synthesis of the AlMepO-β material, which is an aluminophosphate (AlPO) material with methyl groups in its structure.…”
Section: Direct Synthesis Of Hybrid Organic-inorganic Zeolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the first description of full three-dimensional inorganic framework containing organic groups was described by Maeda et al [76]. The authors described the direct hydrothermal synthesis of the AlMepO-β material, which is an aluminophosphate (AlPO) material with methyl groups in its structure.…”
Section: Direct Synthesis Of Hybrid Organic-inorganic Zeolitesmentioning
confidence: 99%
“…Interestingly, Carter et al have shown empirically and by theoretical calculations that AlMepO-α material is thermodynamically more stable than AIMepO-β [80]. Those two materials show high hydrophobic character because of the presence of methyl groups in the channels [76], and consequently, they show unique gas and vapour adsorption properties [82][83][84].…”
Section: Direct Synthesis Of Hybrid Organic-inorganic Zeolitesmentioning
confidence: 99%
“…[9][10][11][12][13] Even when focusing on nanomaterials, a widespread number of investigations can be found. [14][15][16][17][18][19] A good example of such studies is the work of Maeda and colleagues, who have synthesized a novel material, aluminum methylphosphonate-AlMePO-via a hydrothermal route using bohemite and methylphosphonic acid (MPA) as precursors.…”
Section: Introductionmentioning
confidence: 99%
“…10 11 The precise structural determination of two polymorphs of AlMePO and the investigation of some of their physical-chemical properties were fully accomplished in their subsequent works. [10][11][12][13] Although AlMePO single-crystals are not nanometric (their dimensions range between hundreds of micrometers and several millimeters), [10][11][12][13] the presence of one-dimensional organic lined channels with nanometric diameter envision several nano-related applications, such as catalysis and selective transport. [10][11][12][13] In another interesting work, Lewington and co-workers investigated the surface reactivity of aluminum when covered by self-assembled monolayers of phosphonic acids with different alkyl chains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation